(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
To build directional water transport fabric, cotton knitting fabric was finished with TiO_2 sol by two methods: padding and spray. After finishing, the fabrics were irradiated in a self-made UV light box, during which the water contact angle and directional water transport ability were tested. It was found that the fabrics's irradiated side turned from hydrophobic to superhydrophilic within 2 hours, and after 2 hours's irradiation they would recover to hydrophobic within 2 hours. The fabric's directional water transport ability increased with the extend of irradiation time. The sprayed fabric responded more quickly than the padded fabric and took less time to recover than the padded fabric. But the padded fabric had higher maximum one-way water transport capacity.